Acutil® in Mild Cognitive Impairment or Early Dementia: An Exploratory Observational Pilot Study - Rainer, Michael; Mucke, Hermann A.M. (Current Psychiatry Research and Reviews, 2021)
Background: With no approved treatment for mild cognitive impairment (MCI), attention increasingly turns to qualified food supplements. Objective: To conduct a 12-month rater-blinded exploratory outpatient trial with Acutil®, a supplement consisting of ω-3 polyunsaturated fatty acids, Ginkgo biloba extract, and vitamins, in 50 persons with amnestic MCI or mild to moderate Alzheimer or mixed-type dementia. Methods: The used cognitive tools were the Alzheimer's Disease Assessment Scale- Cognitive Subscale (ADAS-Cog), the Mini-Mental State Exam (MMSE), and Controlled Oral Word Association Test (COWAT). Patients were randomized in the ratio of 40:10 to additional Acutil® or no additional supplementation; all continued on their existing medications during the entire study. Results: Only the COWAT produced a clear positive signal in the Acutil® group between individual baseline and study endpoint, but the between-group comparison was not statistically significant. The MMSE score remained stable in the Acutil® group while deteriorating in the control group; post hoc examination suggests that the Acutil® group might have contained responders. The ADAS-Cog and Clinical Dementia Rating (CDR) scores showed marginal deterioration in both groups. Conclusion: We tentatively interpret our results as potentially indicating positive effects of Acutil® on verbal fluency and some aspects of executive function, with an onset after 6 months of continuous treatment. However, much larger and double-blinded studies will be required to make firm statements.
Keywords: dietary supplements